Assessment of Heavy Metal Contamination in Soils and Vegetables in Cameron Highlands Vegetable Farms - Mohamed, El Idrissi AbouJaafar Sidi (2002)
Vegetable cultivation is the most important agricultural activity in Cameron Highlands; about 64% of the population are involved in vegetable cultivation, with a total area of 2 599 hectares. Due to the extensive land levelling and construction of terraces, the vegetables are essentially grown on the subsoil. The subsoil are mainly sandy clay or clay, with large amounts of organic matter being added usually in the form of chicken manure. In a study of assessment of heavy metals in soils and vegetables of Cameron Highlands, Peninsular Malaysia, 200 soil and 40 vegetable samples from various locations were analyzed for cation exchange capacity (CEC), texture, cadmium (Cd), copper (Cu), nickel (Ni), lead (Pb), chromium (Cr) and zinc (Zn), organic carbon COe), pH and available phosphorus (P). The results showed that there was no relationship between total Cd, Cr, Cu, Ni, Pb and Zn concentrations in the soils and in the vegetables. Correlation studies of soil fertility parameters and total heavy metal concentration showed positive correlation between total P and Pb (r =0.492*) and Ni (r = 0.514*). This is indicative of addition of these metals as impurities in organic and inorganic fertilizers Organic Cd showed a positive correlation (r = 0.538*) with soil carbon (OC), while Pb showed a negative correlation (r = - 0.507*). This is indicative of addition of Cd as impurities in organic manures. Copper was positively correlated with clay content (r = 0.678**), while Pb (r = - 0.484*) and Ni (r = -0.554*) were negatively correlated with AI. Pb was negatively correlated with CEC (r = -0.502*). Anova analysis of total Zn, Cd, Cu, Cr, Ni and Pb with soil depth showed a very strong positive relationship. The concentration of Zn, Cd, Cr and Cu are high only in the topsoil (0-20 em), but the concentration of these elements remain the same in the depths of 20-40 em and 40-60 em. This is indicative of the contamination from agriculture activities. The difference in heavy metals from the cultivated soils and the control (primary forest) provides further evidence of the contamination by agriculture activities. The concentrations of heavy metal in Cameron Highlands soils from different vegetable farms were studied. Brinchang and Tanah Rata vegetable farms had very high concentration of Zn (219.80 mglkg); in Brinchang it is above the background values (Dutch Standard Guidelines). Also Brinchang and Tanah Rata farms had very high concentration of eu (61.80 and 71.20 mglkg, respectively), which is above the background level. Cd tends to be high in all Cameron Highlands farm soils.